Immediate Postpartum and Post Abortion Long Acting Reversible Contraception in Referral Level Facility - Muhammad Jamil Johar, Maria Riaz, Farzana Sabir, Sara Akram, Nasreen Akhtar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Despite the advances in the contraceptive technologies, still the unintended pregnancies are adding to the global health issues. The placement of a contraceptive device, such as an intrauterine device (IUD) or contraceptive implant, immediately after childbirth is termed as long-acting reversible contraceptives LARC. Study design: It is a retrospective study conducted at Lady Willingdon Hospital Lahore and Divisional Headquarters Teaching Hospital Mirpur, Azad Kashmir for the duration of six months from April 2022 to September 2022. Material and Methods: The study was approved by the health and ethical board committee of the hospital. The study was conducted on 102 patients that visited tertiary care center during a course of six months. The age of women ranged from 18 to more than 36 years. There were 51 women who belonged to age group 18-24 years, 32 were in the 25-35 year range and 49 were older than 35 years. Results: Standard deviation and p value was calculated and results were statistically significant. There were 8 women who were nulliparous, primipara women were 31 and 58 were multipara. There were 5 women that were included in the grand multipara group. There were 42 women that belonged to urban area and 60 lived in rural area. Most of the women 52 had primary level of education, however 24 had higher secondary level of education and 56 were working women. Conclusion: The acceptance rate was only 9% in the vaginal birth patients. The use of LARC could be an easy and cost effective contraceptive way. Keywords: Intrauterine device and family planning services.